STUDIES ON FROZEN STORAGE OF MINCED FISH FROM THREADFIN BREAM - JOSEPH, JOSE; PERIGREEN, P A (Fishery Technology, 2017)
Minced fish prepared from threadfin bream ( Nemipterus japonicus) was frozen as blocks, packed in polythene lined waxed cartons and stored at - 23Â°C. The changes taking place during storage were followed. There was good correlation between the organoleptic quality, extractability of protein, cook drip loss and weight loss on thawing. The frozen minced fish was acceptable upto 28 weeks under frozen storage.